Harmless or Threatening? Interpreting the Results of Molecular Diagnosis in the Context of Virus-Host Relationships - Abade dos Santos, Fábio A.; Portela, Sara J.; Nogueira, Teresa; Carvalho, Carina L.; de Sousa, Rita; Duarte, Margarida D. (Frontiers in Microbiology, 2021)
Molecular methods, established in the 1980s, expanded and delivered tools for the detection of vestigial quantities of nucleic acids in biological samples. Nucleotide sequencing of these molecules reveals the identity of the organism it belongs to. However, the implications of such detection are often misinterpreted as pathogenic, even in the absence of corroborating clinical evidence. This is particularly significant in the field of virology where the concepts of commensalism, and other benign or neutral relationships, are still very new. In this manuscript, we review some fundamental microbiological concepts including commensalism, mutualism, pathogenicity, and infection, giving special emphasis to their application in virology, in order to clarify the difference between detection and infection. We also propose a system for the correct attribution of terminology in this context.